Fatty acid profile, phytochemicals, and other substances in Canarium odontophyllum fat extracted using supercritical carbon dioxide - Khoo, Hock Eng; Azlan, Azrina; Abdul Kadir, Noor Atiqah Aizan (Frontiers Research Foundation, 2019)
This study aims to identify potential phenolic compounds, terpenoids, and other phytochemicals, as well as fatty acid profile and peptides in Canarium odontophyllum (CO) oil and oleoresin, extracted using supercritical carbon dioxide. LC-ESI-MS was applied in separation and tentative identification of phytochemicals in CO oil and oleoresin. Based on the results, 11 common fatty acids and their isomers, monoglycerides, diglycerides, as well as other types of lipid, were tentatively identified in the CO oil and oleoresin. The identified fatty acids consisted of saturated fatty acids (C8–C16), monounsaturated fatty acids (C16:1 and C18:1), polyunsaturated fatty acids (C18:2, C18:3, C18:4, and C20:3), and other unclassified fatty acids. The tentatively identified phenolic compounds were phenolic acids, flavonoids, lignans, and a phenolic monoester. Triterpenes, sesquiterpenes, and apocarotenoids were the terpenoids found in CO oil and oleoresin. Besides these typical bioactives, some volatiles, aromatic compounds, peptides, and other known and unknown phytochemicals were also tentatively identified in the oil and oleoresin of CO. Some of these compounds are new compounds identified in CO oil and oleoresin, which are not found in many other fruit oils. Although CO oil and oleoresin contain a small number of phytochemicals, their contribution as antioxidants may prevent several diseases. In this study, we hypothesized that CO oleoresin contains certain types of fatty acids that render its semi-solid together with other chemical components which are not found in CO oil. This is the first study that tentatively identified fatty acids, peptides, and potential phytochemicals in CO oil and oleoresin using LC-ESI-MS.